A non-proteolytic function of ubiquitin in transcription repression - Ada Ndoja; Tingting Yao (Microbial Cell, 2014)
Regulation of transcription is vitally important for maintaining normal cellular homeostasis and is also the basis for cellular differentiation, morphogenesis and the adaptability of any organism. Transcription activators, which orchestrate time and locus-specific assembly of complex transcription machinery, act as key players in these processes. One way in which these activators are controlled is by the covalent attachment of the conserved protein, ubiquitin (Ub), which can serve as either a proteolytic or non-proteolytic signal. For a subset of the activators, polyubiquitination-dependent degradation of the activator controls its abundance. In these cases transcription activation can require protein synthesis as well as internal or external stimulus. In contrast, other activators have been reported to undergo mono- or oligoubiquitination that does not lead to protein degradation. The mechanisms by which monoubiquitination of transcription activators affect their activities have been poorly understood. In a recent study, we demonstrated that monoubiquitination of some transcription activators can inhibit transcription by recruiting the AAA+ ATPase Cdc48 (also known in metazoan organisms as p97 or valosin-contain protein, VCP), which then extracts the ubiquitinated activator from DNA.